Class I treatment with severe dental crowding and mandibular protrusion: a case report (Research, Society and Development, 2022)
The use of Corrective Orthodontics to modifying dental aesthetics, has been increasingly effective in modifying and improving the profile of patients. Objective:  Review the literature on the treatment of Cl I malocclusions with severe dental crowding and to report a clinical case performed in the dental clinic of a private educational institution. Methodology: After dental extraction and fixed orthodontic appliance treatment, the facial and dental aesthetics patient evolution with the diastema presence between dental elements 11 and 21 and supernumerary elements. The case was treated in two phases, with the aim of correcting the dental crowding. In the first phase, the first premolars and a supernumerary tooth were extracted, to initiate the isolated canine retraction and, later, the space closures by means of the retraction of the incisors. In the second phase, after the closure of spaces, the intrusion and molarization verticalization phase was started. For the subject review in case, articles were searched in the Pubmed databases, Lilacs and Scielo and selected 8 articles between the years 2010 and 2019.Results and Conclusions: It was observed that the exodontia provided the necessary spaces for the alignment and leveling of the teeth and the intrusion and mandibular rotation of the molars allowed the mandible to rotate counter clockwise, reducing the convex profile of the patient. At the end of the treatment, a facial response was observed according to the mechanics employed and significant improvement in the dental, facial aesthetics and, consequently, social improvement of the patient.